Monumento Natural Grota do Angico : florística, estrutura da comunidade, aspectos autoecológicos e conservação - Silva, Ana Cecília da Cruz (2011)
This study was developed in an area of Caatinga with 251ha, located in it MONA Grota of Angico, in Sergipe, objectified to determine the floristic composition, to characterize the structure and the community's stadiums of sucession. Were collected angiosperms in the plots and in the trails e demarcated 30 plots, in that the trees or shrubs species had heights and measured circumferences and divided in ecological groups. Were found 174 species belonging to 46 families. The arboreal and shrubby component is composed mainly by individuals in the medium stratum, and the pioneer species prevailed with larger number of individuals and with larger values of importance. To test the hypothesis that in areas of Caatinga is waited that there is a prevalence of species abiotics and that the reproductive phenophases of woody species concentrates on the rainy period, somes ecological aspects were analysed, such as: dispersion syndromes, types of fruits and the reproductive phenological patterns. The characterization of the syndromes and of the types of fruits it was based on the collected fruits of angiosperms, while the phenophases was already certain with base in the collected florid and fructified material of trees and bushes. The zoochory was the type of predominant dispersion. The more common fruits were capsule, baga and vegetable. The phenophases came arranged around the dry period. With the objective of provide information regarding the diversity of the plants of Caatinga and to facilitate its recognition, a guide of field of the flowers and of the fruits collected was elaborated in the study area. It`s expected that the creation of Units of Conservation based on biological approaches is effective in the conservation of the biodiversity. Thus, it was had as objectives to analyze the characteristics of the landscape of that Monument and to identify the existence of menaces antrophics. Some characteristics as size, format and isolation degree were confronted with the main ideas of Ecology of Landscape and the identification of the menaces was based on field observations. Is evidenced that the drawing of the Monument is adapted for the maintenance of the species and that the creation of a Protected Area based on the biological value is shown effective in areas of Caatinga. We identified five threats in 2009: hunting, burning, deforestation, grazing and invasive plants, most of which was reduced in 2010.